Clinical Characteristics of Fibrocalcous Pancreatic Diabetes (FCPD) In Children and Adolescents in a Tertiary Hospital (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Fibrocalculous pancreatic diabetes (FCPD) is a unique form of diabetes secondary to nonalcoholic, chronic, calcific, pancreatitis seen in tropical, developing countries of the world.Objective: The purpose of the present study was to determine the clinical features & the glycemic status of the children and adolescents with FCPD. Methodology: This descriptive study was undertaken in the department of paediatrics and at the data retrieval centre of Bangladesh Institute of Research and Rehabilitation in Diabetic, Endocrine and Metabolic Disorders (BIRDEM).Result: Among Seventy two cases of FCPD patients, majority (69.4%) of the patients were between 11-15 years age group and most (81%) of the study population were female. Most (68%) of them came from rural areas and belongs to lower socioeconomic class. Important clinical presentations were typical symptoms of diabetes mellitus (70.83%), abdominal pain (68.1%) and chronic diarrhoea (36.11%). The study population had poor glycaemic control, their mean ( SD) HbAlc were 16.58 4.07. Cataract was the most common complication (47.2%). Only one patient developed Diabetic Keto Acidosis (DKA).Conclusion: Majority of FCPD were female coming from rural areas with poor socio- economic.J Shaheed Suhrawardy Med Coll, 2014; 6(2):53-56